Stylized Facts of Government Finance in the G-7 - Fiorito, Riccardo (IMF Working Papers; Working Paper ;, 1997)
The stylized facts of government finance in the Group of Seven (G-7) industrial countries show that revenues lag real GDP procyclically, while government spending in most cases fails to lead the economy procyclically. This finding is not confined to transfers but also applies to the wage component of government consumption as well as, in most cases, to government fixed investment. Government deficits are always countercyclical but there is little evidence that stabilization is equally successful in stimulating the economy before shocks materialize.